2010
DOI: 10.1037/a0018159
|View full text |Cite
|
Sign up to set email alerts
|

Are working memory deficits in bipolar disorder markers for psychosis?

Abstract: Working memory deficits have been identified in bipolar disorder, but there is evidence suggesting that these deficits may be markers for psychosis rather than affective disorder. The current study examined this issue by comparing two groups of individuals with bipolar disorder, one with psychotic features and one without psychotic features, with a group of normal controls. Working memory was conceptualized as a multicomponent system that includes auditory and visuospatial short-term stores, executive control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 116 publications
(154 reference statements)
4
23
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9] Moreover, we observed that patients with BDI and BDII had abnormally low volume and/or thickness in medial occipital brain regions, including the cuneus, pericalcarine and lingual cortices. These findings are in line with previously reported deficits in visual processing and perception [36][37][38][39][40] -unrelated to lithium use 41,42 -and also with deficits in working memory tasks 10,[43][44][45][46] that partly engage visual areas of the medial occipital cortex. [47][48][49][50] Hence, it is not farfetched to assume that previously observed deficits in visual tasks in patients with BD might be partly related to neuroanatomical abnormalities in medial occipital brain regions.…”
Section: Cortical Abnormalities In Patients With Bdi and Bdiisupporting
confidence: 82%
“…[3][4][5][6][7][8][9] Moreover, we observed that patients with BDI and BDII had abnormally low volume and/or thickness in medial occipital brain regions, including the cuneus, pericalcarine and lingual cortices. These findings are in line with previously reported deficits in visual processing and perception [36][37][38][39][40] -unrelated to lithium use 41,42 -and also with deficits in working memory tasks 10,[43][44][45][46] that partly engage visual areas of the medial occipital cortex. [47][48][49][50] Hence, it is not farfetched to assume that previously observed deficits in visual tasks in patients with BD might be partly related to neuroanatomical abnormalities in medial occipital brain regions.…”
Section: Cortical Abnormalities In Patients With Bdi and Bdiisupporting
confidence: 82%
“…Our results are in line with previous reports showing no significant differences in performance between BPD(+) and BPD(−) on FDS (Glahn et al, 2007;Selva et al, 2007;Martinez-Aran et al, 2008;Savitz et al, 2009;Allen et al, 2010;Brissos et al, 2011) and BDS (Glahn et al, 2007;Selva et al, 2007;Martinez-Aran et al, 2008;Savitz et al, 2009;Allen et al, 2010;Brissos et al, 2011). However, some authors were able to observe differences in cognitive performance between those two groups of patients on these tests (Glahn et al, 2006;Simonsen et al, 2011).…”
Section: Comparison Of Cognitive Performance Between Bpd(+) and Bpd(−supporting
confidence: 75%
“…(Pearlson et al, 1995;Strasser et al, 2005;Glahn et al, 2007;Cui et al, 2011;Anticevic et al, 2014). This hypothesis has been supported by findings showing that BPD patients with psychotic symptoms [BPD(+)] perform worse than BPD patients without psychotic symptoms [BPD(−)] on a variety of neurocognitive measures (Glahn et al, 2006(Glahn et al, , 2007Bora et al, 2007;Martinez-Aran et al, 2008;Allen et al, 2010;Simonsen et al, 2011;Ivleva et al, 2012). In the recent meta-analytic study, a history of psychotic symptoms in BPD was found to be associated with moderately greater impairment in planning and reasoning, working memory, verbal memory and processing speed (Bora et al, 2010).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Allen et al 58 reported unimpaired performance in bipolar patients in memory tasks that are dependent on the episodic buffer. They used tests of verbal and visual learning (California Verbal Learning Test and Biber Visual Learning Test), but they did not include a delayed recall task to assess the consolidation of the learned information.…”
Section: Accepted Manuscriptmentioning
confidence: 98%